Preparation and Characterization of Polyaniline/Fe2O3 Nanocomposite using Surfactant - Eisazadeh, H.; Tanzifi, M. (Asian Journal of Chemistry, 2011)
Nanocomposites of polyaniline containing ferric oxide were synthesized by a chemical method using sodium dodecylbenzenesulfonate as a surfactant. Characteristics of the products such as morphology, particle size and chemical structure were studied. The results indicated that these properties were dependent on the surfactant and metallic oxide were used.